Modern determinants of regional development (on the example of Poland and Turkey) - Miszczak, Katarzyna (Publishing House of the Wrocław University of Economics, 2009)
At the beginning of this new millennium, regional economies are confronting important changes. The globalization of trade and economic activity is increasingly testing their ability to adapt and maintain their competitive edge. There is a tendency for income and performance gaps to widen between and within regions, and the cost of maintaining social cohesion is increasing. On the other hand rapid technological industry and greater use of knowledge are offering new opportunities for local and regional development but demand further investment from enterprises, reorganization of labour and production, more advanced skills and environmental improvements [Territorial review... 2008]. What is more, globalization accelerates changes in law and political emancipation of local and regional societies. As a verification D. Bell’s sentence can be quoted. He believes that the paradox of modern country is that it is too small to manage the global challenges and at the same time too big to solve regional (local) problems effectively [Szczepański 1992, pp. 155-156]. The only solution of this situation is subjecting of local and regional societies. However, this happens at different intensity in different regions. We may distinguish such regions with many resources and high potential, which cope with new conditions very well and become leaders, however they are the minority. Others which lose because they cannot handle the competition and finally these ones which do not even try to compete and become peripheral regions. Doubtless the endogenous factors, which are becoming an important element of competitiveness in the global economy, are more and more important in the new conditions. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 324-333